Fodder grass productivity and soil fertility changes under four grass+tree associations in Kerala, India - B. M. Kumar, S. J. George & T. K. Suresh (Agroforestry Systems 52: 91-106, 2001., 2001)
peninsula, but knowledge of the interactive effects between trees and grasses on their production is limited. We, therefore, conducted a field experiment involving combinations of four trees and grasses, besides monospecific grass controls, for seven years, to investigate grass productivity in association with leguminous and non-leguminous multipurpose trees (MPT) having disparate canopy architecture, and to assess the end-of-rotation soil fertility changes. Post rotation changes in herbage productivity were evaluated by growing teosinte (Zea mexicana) for three years. The four MPTs were Acacia auriculiformis, Ailanthus triphysa, Casuarina equisetifolia and Leucaena leucocephala. Grasses included Pennisetum purpureum (hybrid napier), Brachiaria ruziziensis (congo signal), Panicum maximum (guinea grass) and teosinte. Lower tree branches were pruned from fifth year. Understorey herbage production increased until three years in all tree+grass combinations, but declined subsequently, as tree crowns expanded. Overall, casuarina among MPTs, and hybrid napier and guinea grass among forage crops, were more productive than others. Pruning MPTs generally favoured greater herbage production. Understorey light levels for acacia, ailanthus, casuarina and leucaena were 17, 60, 55 and 55 per cent of that in the open at five years. During the post-rotation phase, MPT plots were characterised by higher soil nutrient capital and consequently teosinte yields were higher than in the treeless control treatment. All previous tree-grass combinations showed an increasing trend till two years after MPT felling. Yield levels declined subsequently, despite at variable rates. Careful selection of the tree and grass components is, therefore, crucial for optimising herbage productivity in silvopastoral systems.